Consumption behavior and residential food waste during the COVID-19 pandemic outbreak in Brazil - Gomes Haensel Schmitt, Valentina (2021)
The objective of this research was to look into the self-reported food consumption and wastage behavior in Brazil during the COVID-19 pandemic outbreak and the motivations to prevent this waste. The data were collected during the COVID-19 pandemic outbreak in Brazil, May 2020, using a self-administered questionnaire with 60 questions on food consumption behavior and characterization of food waste behaviors. The target audience comprised Brazilian residents responsible for household food purchases; out of 489 responses, 458 were considered valid. The main findings reported that regarding consumption behavior, there are no significant differences in relation to gender, education, and age. The surveyed population preferred shopping in person, despite the recommendation of social distancing, and reported activities to avoid food waste. This behavior suggests the importance of information and consumers’ education in making purchases and reducing waste, mainly amidst a crisis. The results suggest that intention to reduce waste, routines of food purchase in sales and management routines of leftovers or uneaten food are positively related to reducing the economic value of food waste. As a practical contribution, this study expands the understanding in one Latin American country regarding food consumption and wastage. The theoretical contribution leads to understanding of the behavior in times of crisis such as a pandemic.